Primary Carcinoid Tumor of the Testis: A Case Report and Review of the Literature - Rawad Abou Zahr; Khalil Chalhoub; Elias Mansour; Camil Chouairy; Georges Ghazal; Joe Nohra (Case Reports in Urology)
Carcinoid tumors usually arise in the gastrointestinal tract. Immunocytohistochemical and radiologic studies are important in detecting the primary tumor site. Primary carcinoid tumors of the testis are particularly rare with a high malignant potential warranting long-term follow-up. We present the case of a primary carcinoid tumor of the testis with long-term surveillance.